Фронтові дороги поета Івана Гончаренка: Київ-Одеса-Севастополь (на матеріалі родинного архіву) - Силка, Оксана Захарівна; Береговий, Сергій Ігорович (My University, 2019)
У статті висвітлено життєвий шлях та схарактеризовано перші літературні здобутки українського радянського поета Івана Івановича Гончаренка (1908–1988). Особливу увагу звернено на період 1941–1942 рр. – участь письменника у військових діях Другої світової війни, зокрема в обороні Одеси й Севастополя. Відзначено, що життєвий і творчий досвід І. Гончаренка є цінним сегментом у вивченні історії спеціального загону українських письменників-фронтовиків. Розвідку написано на основі приватних документів І. Гончаренка (спогадів, епістолярію, маргіналій), що зберігаються в родинному архіві його нащадків, передусім кандидата історичних наук, доцента С. І. Берегового. Детально проаналізовано мотиви воєнних подій та військових дій у творчому доробку поета. The article highlights the way of life and characterizes the first literary achievements of the Ukrainian Soviet poet Ivan Ivanovych Honcharenko (1908–1988). A special attention was paid to the years 1941–1942 – the period of time whenI. Honcharenkoparticipated in themilitary actions of the Second World War, in particular, in the defence of Odessa and Sevastopol. It is emphasized that the poet’s life and his creative experience are valuable components for studying the history of a special detachment of Ukrainian front-line writers who were seconded to the army. For the objective coverage of events in the life of the front-line writer in 1941–1942, based on I. Honcharenko’s personal documents (memoirs, epistolary, marginalia) from the private family archive, highlighted the period of his life from the first war days in Kyiv to the evacuation from Sevastopol in late May 1942. The documents are kept in the family archive of the poet’sdescendants, in particular, in the archive of the Candidate of Historical Sciences, associate professor S. I. Berehovyi. The military events and hostilities in the poet’s literary work were analysed in detail. Research methodology is based upon the work of French historical school “Annals” by applying the concepts of “mentality” and “author’s ego” in the understanding of its representatives. I. Honcharenko began his literary career in 1923withsome publications in the magazine “Molodyi Bolshevik” and the newspaper “Chervona Lubenshchyna”. During that period a number of lyric poetry was created. Over time, Ivan Honcharenko joined the Ukrainian writing cohort. He had close personal and professional relations with P. Tychyna, M. Rylskyi, A. Malyshko and many other representatives of the literary environment. Numerous testimonies of their friendship (letters, telegrams, gift inscriptions) are stored in the family archive. I. Honcharenko was among the defenders of Odessa, Sevastopol and Stalinhrad. He was a correspondent for the Army newspapers, working as a journalist and as a poet. He published two collections of the front lyrics “Odessa. Sevastopol” and “Prymortsi”. The family and private documentary collections of the creative and epistolary heritage of the Ukrainiansoviet writers are among the additional and equally important sources for the study of their personalities in the context of the era. Actually, a part of Ivan Honcharenko’s documentary legacy, which is kept in the family archive, allowed us to analyse his life and creative path in 1941– 1942. We consider the problem development of interpersonal communication of the Ukrainian writers as the participants of military actions of the period to be promising.
Keywords: кафедра гуманітарних дисциплін; українська література; поезія; Ukrainian literature; poetry